‘GROWING UP’ WITH TRAUMA: CHILD ABUSE AND MENTAL ILLNESS IN DAVE PELZER’S MEMOIRS - P, Kavya Shree (ShodhKosh: Journal of Visual and Performing Arts, 2023)
Child abuse is prevalent throughout the world in various forms. Physical abuse, the most common form, has been taken into focus for this research paper. However, open discussions of child abuse are often silenced, especially when the abuser is the child’s parent. ‘Abuse’ by parents is usually considered a way of disciplining the child. Abuse at an early stage leads to various mental illness as children grow into adults. In most cases of child abuse, the victim transforms into an abuser. Factors like suppressed emotions, familiar environments, and lack of companionship push them to extremism and violent action. These individuals are called maladaptive individuals, and the victim-to-victimizer paradigm explains the process of maladaptiveness. On the other hand, some people break the cycle of violence, leaving behind the horrific past of pain and suffering. They thereby transform into adaptive individuals. In this context, the paper reads the novels A Child Called ‘It’, The Lost Boy, and A Man Named Dave, collected into one memoir, My Story, by Dave Pelzer. My Story surveys the author’s life who was physically and emotionally abused as a child by his mentally deranged alcoholic mother. After crossing several hurdles, Dave becomes a successful man inspiring million worldwide. The novels can also be read as Bildungsroman and Künstlerroman, as the author is growing to maturity in dealing with and writing about trauma. In the process, Dave overcomes trauma and establishes himself as a successful person and an artist. He ‘grows up’ as a child abuse victim; however, he grows out of it by accepting his past and looking forward to what the future holds for him.